Serving Up Chineseness: Myths of Authenticity and Identity in Kylie Kwongâ€™s Cookery Texts - Huiyi, Monash University Malaysia, Jacqui Kong (Asiatic: IIUM Journal of English Language and Literature, 2016)
This paper seeks to examine the form and content of the culinary television programmes and cookbooks of Australian-Chinese celebrity chef and restaurateur, Kylie Kwong. It will utilise Bill Nicholsâ€™ theory of â€œThe Challenge of Persuasionâ€ to demonstrate how Kwongâ€™s cookery show, Kylie Kwong: Cooking with Heart and Soul, is not just about food and cooking, but embodies particular ideologies and â€œmyths,â€ as theorised by Barthes, about Chinese culture and identity. It also draws upon selected excerpts from Kwongâ€™s cookbooks and food memoir, Kylie Kwong: Recipes and Stories (2003) and My China: A Feast for the Senses (2007), to unpack their representations of Chinese culture and identity. My aim is to elucidate how Kwongâ€™s cooking show and cookbooks transcend their pragmatic function to become representational tools that carry specific meanings about Chineseness, both in terms of its production and consumption.